Reversal of spatial memory impairment by phosphodiesterase 3 inhibitor cilostazol is associated with reduced neuroinflammation and increased cerebral glucose uptake in aged male mice - Yanai, Shuichi; Tago, Tetsuro; Toyohara, Jun; Arasaki, Tomoko; Endo, Shogo (Frontiers in Pharmacology, 2022)
The nucleotide second messenger 3’, 5’-cyclic adenosine monophosphate (cAMP) and 3’, 5’-cyclic guanosine monophosphate (cGMP) mediate fundamental functions of the brain, including learning and memory. Phosphodiesterase 3 (PDE3) can hydrolyze both cAMP and cGMP and appears to be involved in regulating intracellular cAMP content. We previously demonstrated that long-term administration of cilostazol, a PDE3 inhibitor, maintained good memory performance in aging mice. Here, we report on studies aimed at determining whether cilostazol also reverses already-impaired memory in aged male mice. One month of oral 1.5% cilostazol administration in 22-month-old mice reversed age-related declines in hippocampus-dependent memory tasks, including the object recognition and the Morris water maze. Furthermore, cilostazol reduced neuroinflammation, as evidenced by immunohistochemical staining, and increased glucose uptake in the brain, as evidence by positron emission tomography (PET) with 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG). These results suggest that already-expressed memory impairment in aged male mice that depend on cyclic nucleotide signaling can be reversed by inhibition of PDE3. The reversal of age-related memory impairments may occur in the central nervous system, either through cilostazol-enhanced recall or strengthening of weak memories that otherwise may be resistant to recall.